STUDY TO DETERMINE THE ASSOCIATION BETWEEN INFLAMMATORY MARKER (C-REACTIVE PROTEIN) AND HBA1C IN PATIENTS WITH TYPE 2 DIABETES MELLITUS - Nirala, Rakesh Kumar; Priya, Jyoti (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: Patients with type 2 diabetes exhibit subclinical inflammation and nearly all signs of systemic inflammation, which characterized by high circulating levels of inflammatory parameters. The present study aimed to assess the levels of the inflammatory markers such as C-reactive protein (CRP) in patients with type 2 diabetes mellitus and to correlate their values with the hemoglobin A1c (HbA1c) levels. Methods: This cross-sectional study was conducted on 78 patients with type 2 diabetes in Patna Medical College and Hospital, Patna. All patients had laboratory investigations including HbA1C and CRP, patients were assessed according to glycemic status, patients with under control of diabetics (HbA1C level was equal to or <6.5%), and patients with poorly-controlled diabetics (HbA1c level was >6.5%). Results: Statistically significant association was observed between CRP levels and level of HbA1c. The CRP level was significantly higher in poorly-controlled diabetic patient than who with well-controlled diabetics (p=0.017). Conclusions: There is positive correlation between the level of glycemic control (HbA1c) and CRP levels; better glycemic control results in significant reduction in the highly sensitive C-reactive protein levels.